Analisis Penerapan Tata Cara Shalat yang Benar pada Santri TPA Geuceu Meunara Banda Aceh - Burrahman, Muji; Faridy, Faizatul (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
The implementation of this community service aims to develop and dedicate knowledge to the community to help and awaken children and the community in science and worship. In this study, we utilized counseling and demonstrations, counseling using lectures i.e. delivering material about prayer services, and practicing prayer procedures both from the reading as well as the gestures in prayer. This study found that the children (santri) of TPA Geuceu Meunara Banda Aceh feel very pleased and enthusiastic in following the materials and demonstrations of prayers.